Analisis Sistem Pendukung Keputusan Dalam Rekomendasi Kenaikan Pangkat PNS Menggunakan Kombinasi Metode TOPSIS dan SAW - Anisa Agustina Melani; Lukman Bachtiar (STMIK Budi Darma, 2022)
PNS promotion is an award given to Civil Servants who have met the specified requirements as well as for work performance and service to the country. a Civil Servant is required to continue to be able to apply for promotions periodically to the highest level, so that within a certain period of time every civil servant gets the opportunity to apply for promotions. Similar to the scope of the East Kotawaringin Regional Secretariat, civil servants have the right to apply for a promotion every 4 years. The Staffing of the Regional Secretariat of the Kotim has difficulties in selecting the file for promotion proposals because of the large number of employees who propose promotions and the files and provisions gathered by civil servants must be managed immediately so that they are submitted to the BKPSDM. Researchers offer a decision support system with TOPSIS and SAW methods. The combination of the two methods serves to produce optimal decisions in accordance with predetermined criteria. This study uses 5 alternatives and 4 criteria. In this study, the alternatives consisted of Kurniawan Wibowo, Idris Sugiono, Nuringsih Sujati, Meuthia Rakhmasari, and Maulana. Of the five alternatives, those with the highest final score were Idris Sugiono, Nuringsih Sujati and Meuthia Rakhmasari with a value of 0.427 or 42.7%.